School-Based Prevention Targeting Non-Suicidal Self-injury: A Pilot Study - Baetens, Imke; Decruy, Christine; Vatandoost, Shokoufeh; Vanderhaegen, Birgit; Kiekens, Glenn (Frontiers in Psychiatry, 2020)
Non-suicidal self-injury (NSSI) is prevalent in adolescence and is associated with increased risk for a variety of subsequent negative mental health outcomes, necessitating an evidence-based preventive approach. This pilot study examines the potential iatrogenic effects and feasibility of an evidence-based school program for the prevention of NSSI. Differences are examined between a general in-classroom prevention program (Happyles) and this program combined with a 1-h in-classroom psychoeducation module on NSSI (HappylesPLUS) in terms of primary (e.g., delay in NSSI onset and decrease in NSSI frequency, urges, probability of future engagement) and secondary outcomes (e.g., psychological distress, emotion regulation, help-seeking, and stigma) using a mixed-method design. A total of 651 secundary school pupils (Mage = 12.85 years; 49.8% female versus 50.2% male) were assigned to the Happyles program and HappylesPLUS. Participants filled out validated self-report questionnaires pre (T0) and post (T1, 6 weeks after T0) the school prevention program, including the Youth Outcome Questionnaire (YOQ), the Brief Non-Suicidal Self-Injury Assessment Test (BNSSI-AT), the Difficulties in Emotion Regulation Scale (DERS), the Attitudes Toward Seeking Professional Psychological Help Scale—Short Form (ATSPPH-SF), and the Peer Mental Health Stigmatization Scale (PMHSS). Qualitative semi-structured interviews (at T2,6 weeks after T1) were conducted with participants with and without a history of NSSI. Overall, results show no iatrogenic effects of the NSSI-focused psychoeducation module. In terms of our primary outcome, both groups reported a reduced likelihood of future NSSI engagement from T0 to T1. Regarding secondary outcome measures, we also observed increased emotional awareness in both groups. The qualitative data suggest that the addition of the NSSI-specific module to the Happyles program may have direct benefits to some students with lived experience, such as increased help-seeking behavior for NSSI. Findings of this pilot study show that incorporating NSSI-specific modules into evidence-based school prevention programs is feasible and does not lead to iatrogenic effects. Future work is needed to evaluate the potential (longer-term) benefits of incorporating NSSI-focused modules to evidence-based mental health programs in the prevention of NSSI.